ANALISIS PEMBAGIAN WAKTU WANITA DALAM RUMAH TANGGA NELAYAN KECAMATAN LABUHAN MARINGGAI KABUPATEN LAMPUNG TIMUR - Novia Ambar Sari; Titin Liana Febriyanti (Universitas Pattimura, 2021)
The result of this search is to identify the time sharing by women fishermen household for domestic, productive and social activities and to identify alternative activities carried out by women fisherman households in the use of their leisure time. This research was conducted in Muara Gading Mas Village purposively in November 2021, with simple random sampling of 100 respondents. The method used in this research is survey method, data collection is done by questionnaire, observation, and literature study with primary data and secondary data. The results showed that the time allocated by female fishermen in the household was divided into domestic activities, productive activities, and social activities. Of all the time allocations made by women in fishing households, the remaining time allocation is called free time. By looking at the resources that have not been optimized, the allocation of free time can be done by doing useful activities with the available resources. Some of the things above show that household women can still carry out useful activities that can increase productivity and can help the family economy. Activities that can be done are to make processed foods and crafts from shellfish waste.